2019
DOI: 10.1002/batt.201900019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Polydopamine Interlayer on the Long‐Term Cycling Performance of Silicon Anodes: A Multiphysics‐Based Model Study

Abstract: To understand the effect of a polydopamine interlayer between a copper current collector and a silicon composite electrode, a physics-based model is used to analyze the cycle performance of silicon-based lithium-ion half-cells with bare and polydopamine-treated copper current collectors. We investigate the capacity-fading mechanisms of the two cell configurations by analyzing the model parameters that change with cycling. The major capacity-fading mechanisms in the silicon-based anodes are the increase in film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This resulted in a decrease in the rate constant for electron transfer in the BV equation. 15 Figure 4c shows the relationship between the rate constant (k p ) and number of cycles for Li/Si cells with PD-treated and bare copper foil. At the beginning of cycling, electrons tunnel through the PD-laminate, which leads to a reduction in the rate constant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This resulted in a decrease in the rate constant for electron transfer in the BV equation. 15 Figure 4c shows the relationship between the rate constant (k p ) and number of cycles for Li/Si cells with PD-treated and bare copper foil. At the beginning of cycling, electrons tunnel through the PD-laminate, which leads to a reduction in the rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,25,26 Modeling of SEI formation.-For Si-based electrodes, it has been reported that, two types of SEI are formed during the (de) lithiation processes. First is the formation of diethyl methyl 2,5dioxahexane dicarboxylate (DEDOHC) 26 during the initial stages of cycling when a mixture of ethylene carbonate/diethyl carbonate (EC: DEC) related solvents are used for the electrolyte and ethyl methyl 2, 5-dioxahexane dicarboxylate (EMDOHC) 15 when a mixture of z E-mail: mhryou@hanbat.ac.kr; yongmin.lee@dgist.ac.kr *Electrochemical Society Student Member. ethylene carbonate/ethyl methyl carbonate (EC:EMC) related solvents are used.…”
Section: Chemo-mechanical Degradation Modelmentioning
confidence: 99%
See 3 more Smart Citations